2013
DOI: 10.3329/bjvm.v9i2.13451
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Threat Caused by Zoonotic Diseases in Bangladesh

Abstract: Diseases and infections shared between animals and humans are mainly called zoonotic diseases which may be categorized as emerging, reemerging and neglected. All types of these diseases occur t  hroughout the world including Bangladesh. The results on the prevalence and effects of zoonotic diseases in humans and animals of Bangladesh are analyzed from the published literatures and presented in this report. It appears from the literature that there are about 1415 human pathogens of which 61% are zoonotic and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 74 publications
1
55
0
Order By: Relevance
“…Despite sanitation efforts and control measures, in a limited scale, outbreaks of zoonotic diseases are frequent in Bangladesh [47]. According to this study, the level of hygienic and bio-safety measures, e.g., regular hand washing, use of disinfectants, cleaning of the utensils, and washing of the floors and cages are very poor in poultry farms and markets.…”
Section: Discussionmentioning
confidence: 92%
“…Despite sanitation efforts and control measures, in a limited scale, outbreaks of zoonotic diseases are frequent in Bangladesh [47]. According to this study, the level of hygienic and bio-safety measures, e.g., regular hand washing, use of disinfectants, cleaning of the utensils, and washing of the floors and cages are very poor in poultry farms and markets.…”
Section: Discussionmentioning
confidence: 92%
“…Household pets have been found to play a direct role in transmitting zoonosis (Dada et al, 1979;Kornblatt and Schantz, 1980). Review of literatures revealed that at least 36 important zoonotic diseases are acquired from dogs worldwide, although the occurrence of some important zoonotic diseases acquired from dogs have reported from Bangladesh but the inland reports on this aspect are very limited (Samad, 2011). Domestic dogs pose a significant risk as reservoirs for infectious diseases, especially for wild canids (Bronson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Salauddin (2015) isolated E. coli in all the samples of broiler and found some isolates of E. coli were multi drug resistant. Islam et al (2010) characterize shiga-toxin producing Escherichia coli in raw meat, raw milk in Bangladesh .Food borne diseases including colibacillosis are a significant and widespread global public health threat reported in Bangladesh (Samad, 2011;Zakaria et al, 2011). Hence the objectives of this study were to isolate and identify antimicrobial resistant E. coli from chicken meat, beef and milk samples in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%